The hidden history of the historic fundamentalists, 1933 - 1948: reconsidering the historic fundamentalists' response to the upheavals, hardships, and horrors of the 1930s and 1940s - Owen, Jim (Univ. Press of America, 2004)
Conventional scholars portray the historic fundamentalists as theologically challenged, politically indifferent, social uncaring, and economically a bare step above Social Darwinian Neanderthal, accuses Owen (history, The Master's College, Santa Clarita, California). Inspired to vindicate his spiritual antecedents and armed with the tools of his pr